Multi-Scalar Drivers of Residential Vegetation Changes in Metropolitan Phoenix, Arizona. - Zhu, Qinnan; Larson, Kelli L. (Environmental Management, 2024)
In the arid southwestern U.S., urban greening strategies have been promoted to alleviate ecosystem disservices associated with lawns, including the adoption of xeric yards with desert-adapted floras and gravel groundcover and wildlife-friendly yards with complex vegetation structure and composition. Scant studies have investigated the extent of different vegetation changes in urban greening practices and the complexity of associated human drivers. We addressed this gap by analyzing survey data from two survey periods (2017 and 2021) to answer the following questions: to what extent have residents from metropolitan Phoenix made different vegetation changes in their yards over the last decade, and how do multi-scalar human drivers affect different vegetation changes? We found a sustainable trajectory for residential vegetation changes in Phoenix since mid-2010s, with declining additions of grass and increases in trees and desert plants across residential neighborhoods. Esthetics was an influential driver of both tree planting and native gardening. Additionally, tree planting was associated with anthropocentric values (i.e., low-maintenance needs), while desert plant additions reflected the appreciation of nature (i.e., attitudes towards the desert) and environmental concerns (i.e., supporting wildlife). Institutions such as local government programs might shape residents' vegetation choices, as tree planting differed among municipalities. We also found counterintuitive influences of residential tenure controls on landscaping decisions. Specifically, renters were more likely to add yard trees compared to homeowners. Our results inform landscape sustainability by identifying potential pathways to residential yard changes that offer a multitude of services while being appreciated and maintained by residents.